2002
DOI: 10.1097/00005537-200204000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Disorders in the Elderly

Abstract: Changes that occur as a natural part of senescence in the complex action of deglutition predispose us to dysphagia and aspiration. As the "baby-boomers" begin to age, the onset of swallowing difficulties will begin to manifest in a greater number of our population. Recent advances in the evaluation of normal and abnormal swallowing make possible more precise anatomical and physiological diagnoses. Coupled with an understanding of swallowing physiology, such detailed evaluation allows greater opportunity to saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
128
0
19

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 105 publications
(157 reference statements)
1
128
0
19
Order By: Relevance
“…One study found that people over the age of 65 may account for two thirds of all people with dysphagia. 19 Medical conditions predisposing patients to dysphagia include stroke, Alzheimer disease, amyotrophic lateral sclerosis, and Parkinson's disease. 3 The prevalence of all these conditions increases with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that people over the age of 65 may account for two thirds of all people with dysphagia. 19 Medical conditions predisposing patients to dysphagia include stroke, Alzheimer disease, amyotrophic lateral sclerosis, and Parkinson's disease. 3 The prevalence of all these conditions increases with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…Presbydysphagien) zukünftig in den Fokus rücken [28,48]. Veränderungen in der mukosalen Sensibilität, sensorische Veränderungen von Geschmacks-und Geruchssinn, eine reduzierte Speichelproduktion, zerebral-degenerative Prozesse und Veränderungen in Qualität und Quantität neuromuskulä-rer Koordinationsprozesse beeinflussen die Schluckleistung im Alter meistens negativ [5,28].…”
Section: » Antikonvulsive Medikamente Können Ein Bestehendes Schluckdunclassified
“…A literatura cita na deglutição de idosos maior ocorrência de diminuição de força, aumento do tempo e diminuição de adaptações a diferentes consistências (41,45) , mesmo em deglutições voluntárias em que o indivíduo, conscientemente, pode buscar as compensações (44) .…”
Section: Discussionunclassified
“…São inúmeros os trabalhos a respeito da anatomia e fisiologia da deglutição em idosos saudáveis, evidenciando os sinais provenientes da deglutição senescente (4,37,38,39,40,41,42,43) .…”
Section: R Re Ev VI Is Sã ãO O D Da a L Li It Te Er Ra At Tu Ur Ra A 21unclassified
See 1 more Smart Citation